Psychological Problems in Ischemic Stroke Patients at the Regional General Hospital Dr. Pringadi Medan 2019 - Wirda Faswita (Jurnal Maternitas Kebidanan, 2019)
ABSTRACT The level of limitation of stroke patients shows a significant relationship to the incidence of emotional distress. A stroke sufferer will suddenly lose many things that are very important and to be proud of. This will be a stressor for self-concept that ultimately causes someone to be disturbed by emotions, feelings and thoughts, causing anxiety, self-esteem disorders and depression. The population in this study were patients with ischemic stroke who were treated in the Neurology Poly Room and were treated in the inpatient room of RSUD Dr. Pirngadi Medan. Researchers took a sample with non-probability sampling with a total sample of 52 people. The purpose of this study was to identify psychological problems in ischemic stroke sufferers at Dr. Pirngadi General Hospital Medan. The research design used was descriptive with univariate analysis using three instruments namely the Beck Anxiety Inventory Instrument, the Rossenberg Self Esteem Scale and The Center of Epidemiological Studies Depression. The research found that the majority of respondents experienced severe anxiety as many as 33 people (63.50%), moderate self-esteem as many as 18 people (34.60%) and depression as many as 39 people (25%). It is expected for nursing practice to better identify the cause of psychological problems experienced by ischemic stroke sufferers so that they can find the right independent action.